Rib Motions Don't Completely Hinge on Joint Design: Costal Joint Anatomy and Ventilatory Kinematics in a Teiid Lizard, Salvator merianae. Issue 1 (2nd January 2019) - Capano, J G; Moritz, S; Cieri, R L; Reveret, L; Brainerd, E L
Abstract: Rib rotations contribute to lung ventilation in most extant amniotes. These rotations are typically described as bucket-handle rotation about a dorsoventral axis, caliper rotation about a craniocaudal axis, and pump-handle rotation about a mediolateral axis. A synapomorphy for Lepidosauria is single-headed costovertebral articulations derived from the ancestral double-headed articulations of most amniotes. With a single articular surface, the costovertebral joints of squamates have the potential to rotate with three degrees-of-freedom (DOFs), but considerable variation exists in joint shape. We compared the costovertebral morphology of the Argentine black and white tegu, Salvator merianae, with the green iguana, Iguana iguana, and found that the costovertebral articulations of I. iguana were hemispherical, while those of S. merianae were dorsoventrally elongated and hemiellipsoidal. We predicted that the elongate joints in S. merianae would permit bucket-handle rotations while restricting caliper and pump-handle rotations, relative to the rounded joints of I. iguana . We used X-ray reconstruction of moving morphology to quantify rib rotations during breathing in S. merianae for comparison with prior work in I. iguana . Consistent with our hypothesis, we found less caliper motion in S. meriana e than in I. iguana, but unexpectedly found similar pump-handle magnitudes in each species. The dorsoventrally elongate costovertebral morphology of S. merianae may provide passive rib support to reduce the conflict between locomotion and ventilation. Moreover, the observation of multiple DOFs during rib rotations in both species suggests that permissive costovertebral morphology may be more related to the biological roles of ribs outside of ventilation and help explain the evolution of this trait.